Fire blight (Erwinia amylovora) resistance in apple varieties associated with molecular markers - Sehic, J.; Nyboom, H.; Garkava-Gustavsson, L.; Patocchi, A.; Kellerhals, M.; Duffy, B. (International Journal of Horticultural Science, 2009)
The invasive bacterial disease fire blight, caused by Erwinia amylovora has the potential to destroy fruit tree orchards all over Europe. Effective plant protection methods are lacking in many countries, highlighting the increasing importance placed on identification of germplasm with heritable disease resistance. Recent l y. a promising QTL (quantitative trait locus) was identified on linkage group 7 in the apple cultivar ’Fiesta· which is derived from ·cox’s Orange Pippin’ . I n the present study, 144 Swedish and foreign apple cultivars were analysed with the SCAR markers AE I 0-375 and GE-8019. which flank-. this QTL. Twenty-nine of the analysed cultivars had both markers. 78 had either AE I 0-375 or GE-8019, and 37 cultivars did not carry an) of the two markers. Seventeen cultivars. 7 with both markers and I 0 not having either of the two markers, were then inocoluted with the bacterium in a 4uaran1i ne greenhouse test. Cultivars carrying both DNA markers were significantly less susceptible than cultivars lacking the markers, P<0.001. Cultivars that were most resistant had both markers and had ’Cox· in their pedigree. Unrelated cultivars with the markers may still lack the QTL.